2008
DOI: 10.1681/asn.2007040490
|View full text |Cite
|
Sign up to set email alerts
|

NEK8 Mutations Affect Ciliary and Centrosomal Localization and May Cause Nephronophthisis

Abstract: Nephronophthisis, an autosomal recessive kidney disease, is the most frequent genetic cause of chronic renal failure in the first 3 decades of life. Causative mutations in 8 genes (NPHP1-8) have been identified, and homologous mouse models for NPHP2/INVS and NPHP3 have been described. The jck mouse is another model of recessive cystic kidney disease, and this mouse harbors a missense mutation, G448V, in the highly conserved RCC1 domain of Nek8. We hypothesized that mutations in NEK8 might cause nephronophthisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
176
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(179 citation statements)
references
References 24 publications
(36 reference statements)
3
176
0
Order By: Relevance
“…Subsequent studies have reported missense mutations in the RCC domain-encoding regions of both rat Nek8 in the Lewis PKD model 16 and human NEK8, in which three independent mutations were identified from 700 NPHP patients, making it a candidate for NPHP type 9. 11,17 Together, these data demonstrate that the NEK8 C terminus is critical for its function and the protein plays an important role in the maintenance of renal tubule integrity in the postnatal kidney. Of note, all of the reported mutations of Nek8 are missense mutations.…”
mentioning
confidence: 79%
“…Subsequent studies have reported missense mutations in the RCC domain-encoding regions of both rat Nek8 in the Lewis PKD model 16 and human NEK8, in which three independent mutations were identified from 700 NPHP patients, making it a candidate for NPHP type 9. 11,17 Together, these data demonstrate that the NEK8 C terminus is critical for its function and the protein plays an important role in the maintenance of renal tubule integrity in the postnatal kidney. Of note, all of the reported mutations of Nek8 are missense mutations.…”
mentioning
confidence: 79%
“…The jck mutant phenotypically resembles ADPKD 29 and carries a mutation in the Nek8 kinase. 36 Mutations in NEK8 have been identified in patients with nephronophthisis-9 37 and in the Lewis PKD rat. 38 At 7 weeks of age, jck/jck mice showed a mean (6SEM) %KW/BW of 4.960.33 (n=11) compared with 1.360.04 in wt mice (n=19).…”
Section: Small Molecule Hh Inhibitors Do Notmentioning
confidence: 99%
“…2 Nek kinases function in the formation of the primary cilium in many eukaryotes. [3][4][5][6][7][8] They also play roles in DNA repair 9 and apoptosis. 10 Spontaneous mutations in genes encoding two members of the Nek family give rise to autosomal recessive forms of polycystic kidney disease (PKD) in the mouse.…”
mentioning
confidence: 99%
“…Nek8 nevertheless regulates the expression and localization of the polycystins 4,20 and has been linked to medullary cystic kidney disease (nephronopthisis). 8 Knockdown of Nek8 in zebrafish embryos results in cystic kidney. 16 Independent investigations have shown that knockouts of TAZ (Wwtr1) result in the development of PKD.…”
mentioning
confidence: 99%